199 HYPERGLYCEMIA PREDICTS FAILURE IN PERCUTANEOUS INTERVENTION OF CORONARY CHRONIC TOTAL OCCLUSION. Issue 1 (1st January 2007) - Khan, Q.; Sachdeva, R.; Malhotra, A.; Reddy, R.; Sukhija, R.; Sarkar, K.; Mehta, J. L.
Abstract : Objective: Hyperglycemia is known to be associated with increased morbidity and mortality in critically ill hospitalized patients. Although the presence of diabetes mellitus is associated with poor outcomes, we sought to determine the effect of periprocedural hyperglycemia on the success of percutaneous intervention (PCI) in coronary chronic total occlusions (CTO). Methods: The study cohort included patients undergoing PCI to open CTO and symptoms of > 1 year's duration. Fasting blood glucose levels were measured on the morning of the procedure day. Postprocedure success, contrast volume, and creatinine elevations were also recorded. Clinical events (death, myocardial infarction, repeat revascularization, and hospitalization for cardiac reasons) over 5 to 12 months of follow-up were recorded. Results: Seventy-two patients, all men, mean age 64 ± 9 years, formed the study cohort. PCI was successful in 34 of 72 (47%) patients. Mean follow-up duration was 6 ± 2 months. Periprocedural glucose level was not a significant predictor for major cardiovascular adverse events (MACE) or a rise in creatinine (multivariate analysis controlling for contrast volume). However, fasting blood glucose was significantly lower in group with successful PCI (128 ± 36 vs 171 ± 52 mg/dL, p = .008). In multivariate analysis after controlling for presence of diabetes, contrast volume, and age, periprocedural hyperglycemia remained the only significant independent predictor of PCI outcome. Conclusions: Periprocedural hyperglycemia is a powerful predictor of outcome for PCI in CTO of coronary arteries. Aggressive preprocedure glycemic control is likely to improve immediate success in opening CTOs.